2013
DOI: 10.1016/j.ijcard.2013.01.207
|View full text |Cite
|
Sign up to set email alerts
|

Valvular osteoclasts in calcification and aortic valve stenosis severity

Abstract: These findings suggest a critical role of bone turnover as a determinant of aortic stenosis severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…14 Circulating and valve tissue levels of RUNX2 significantly correlated with valve stenosis severity. 41 In this study, we demonstrated that 2 SNPs in perfect linkage disequilibrium, rs114193529 and rs144071310, located in intron 1 of RUNX2 were moderately associated with AS. Whether one of these variants is functional or in linkage disequilibrium with another rare variant in RUNX2 is unclear from this study.…”
Section: Discussionmentioning
confidence: 58%
“…14 Circulating and valve tissue levels of RUNX2 significantly correlated with valve stenosis severity. 41 In this study, we demonstrated that 2 SNPs in perfect linkage disequilibrium, rs114193529 and rs144071310, located in intron 1 of RUNX2 were moderately associated with AS. Whether one of these variants is functional or in linkage disequilibrium with another rare variant in RUNX2 is unclear from this study.…”
Section: Discussionmentioning
confidence: 58%
“…In the COFRASA study, Hekimian et al (2013) reported that progression of AVS was associated with calciumphosphorus metabolism and a bone resorptive remodeling. Recently, Nagy et al (2013) found a close relation between circulating mediators of bone homeostasis and severity of AVS.…”
Section: Relation Between Mineral Metabolism Disturbance and Cavdmentioning
confidence: 97%
“…49 In the latter study, treatment with a hypomethylator in addition decreased promoter methylation and increased 5-lipoxygenase transcription and leukotriene production, 49 which may participate in the pathological processes of aortic stenosis. 17 In addition, several genes encoding osteogenic proteins associated with heterotopic bone formation in aortic valves 5,50 are regulated by GC-rich promoters sensitive to methylation/hypomethylation. Interestingly, osteopontin gene methylation is decreased in response to shear stress in murine bone marrow-derived progenitor cells, associated with increased osteopontin expression.…”
Section: Cellular Responses To Biomechanical Factorsmentioning
confidence: 99%